Understanding the 14 February 2024 tornado in Cyprus - Loulli, Eleni; Michaelides, Silas; Bühl, Johannes; Mamouri, Rodanthi-Elisavet; Nisantzi, Argyro; Ene, Dragos; Seifert, Patric; Charalambous, Demetris; Tymvios, Filippos; Hadjimitsis, Diofantos (My University, 2024)
On 14 February 2024, Cyprus experienced a significant damaging tornado, characterized by gale force winds, heavy precipitation, and a distinct spiral pattern of thunderstorms. The event caused extensive damage across Limassol district, particularly in Germasogeia suburb. This work examines the potential of using remote sensing observations for the analysis of convective storms associated with tornadic activity. For the analysis of the tornado, we use meteorological radar data from the Department of Meteorology’s radar stations in Pafos (PFO) and Larnaca (LCA), in synergy with wind-lidar and disdrometer data from the Cyprus Atmospheric Remote Sensing Observatory (CARO), the latter located in Limassol and at a distance of approximately 10km from the tornado funnel. The analysis involves wind speed data, damage reports and photographic evidence to capture the trail of the tornado. Preliminary results provide evidence of a hook echo and velocity couplets in radar data during the early morning hours on 14 February 2024. During the tornado event, CARO recorded vertical wind speeds of up to 10m/s and an instantaneous rain rate of 80 mm/h.
Keywords: tornado; X-Band radar; disdrometer; wind-lidar; radial velocity; reflectivity